A novel hexapod and its prototype for secondary mirror alignment in telescopes. (August 2018) - Yang, De-Hua; Cheng, Ying; Wu, Chang-Cheng; Fei, Fei; Jin, Zhen-Yu
Abstract: This paper presents a novel hexapod as the adjustment mechanism for a telescope to actively align its secondary mirror. The special hexapod provides six degrees of freedom (6-DOFs) with decoupled translation and rotation. The decoupled kinematic motions are analyzed and commented on as the alignment mechanism of a secondary mirror from an optical alignment point of view. In terms of performance of the adjustment generally required by the secondary mirror in a telescope, we developed a prototype that uses a novel hexapod design with linear micro-displacement actuators. Especially, in order to achieve high precision, flexures were used to build joints for the hexapod to minimize frictions and eliminate backlashes. Based on the specific configuration and dimension of the prototype hexapod, an analytical model of the reachable workspace was built with the constraints defined by limited rotation angles of the flexure-based joints. We used a laser tracker to verify that the hexapod can reach a spherical translation workspace of ϕ 6 mm and a rotation workspace of ± 1°. The translational repeatability was tested to be around half a μ m by laser displacement sensors. In addition, we also measured the axial and lateral stiffnesses of the hexapod to be around 5500 N mm −1 and 1750 N mm −1, respectively. The kinematic analyses and convincing test results jointly encourage implementing the novel hexapod design with decoupled translation and rotation as a favorable alignment mechanism for secondary mirrors in astronomical telescopes.